Application of Digital-Based Marketing Strategies in Snack Businesses to Improve Student Entrepreneurship Spirit - Erma Novela; Anggen Dari; Jessica Artsheila Anggraini; Puan Aisyah Maharani (CV. Media Inti Teknologi, 2023)
The increasingly sophisticated development of technology causes marketing trends to continue to grow, where marketing shifts from conventional to the digital world. Digital marketing provides many conveniences ranging from offering products, wider marketing reach and lower marketing costs. This study aims to determine the application of digital-based marketing strategies in snack businesses to improve the entrepreneurial spirit of students. The research method used is qualitative discriptive. Data sources were obtained from interviews with informants, as well as questionnaires and observations. The results showed that the application of digital-based marketing strategies in snack businesses can increase basreng sales three times more than direct marketing and is considered very attractive with a percentage of 60% with the coupon method and basreng products that are marketed have received a good response with a percentage of 80%.